(untitled) (Revista Innova Educación, 2022)
Objective: The purpose of this work was to expose the qualities and capacities that adapted, Paralympic and inclusive sport possesses, its effect of abolition on a series of discriminatory stereotypes against functional diversity, limitations that are still maintained in certain societies. Various realities are analyzed where inclusive government policies have been developed based on physical-sports practices in populations with disabilities, detailing the specific case of Ecuador. Method: This research was based on a documentary-bibliographical exploration, using the following databases: Psycinfo, Medline, Ebsco, Scielo, Psicodoc, PsycArticles, and the main repositories of postgraduate institutions. Within this selection procedure, only bibliographic material published within a range of the last five years was considered. Under these criteria, 75 papers were obtained, of which 33 were selected, of which 9 doctoral theses and a master’s thesis with material directly related to the research proposal stand out. Results: The need to respect human rights in people with disabilities is evident, the urgency of being actively included in a society, among some points the practice of recreational, cultural and sports activities. These action mechanisms allow the breaking of stereotypes, consolidate the family environment and the internal world of the person with different capacities. Conclusions: Educational inclusion through sport is a strategy on which developing European countries are based. In Ecuador there are very low levels of physical-sports practices in people with functional diversity, a responsibility that falls on the government function, a structure that promotes improvement and growth in health and sports at the level of the population with disabilities.